(untitled) (Conferencea, 2022)
This research aimed at studying the student’s problems in speaking English language program at Secondary education schools in Uzbekistan. This study tried to find the students’ problems, the factors cause the problems in speaking at Uzbekistan schools. This research was based on the fact that the students still have some problems in speaking English, although they have been encouraged to use English in daily program. During the investigation of research study, I have witnessed following issues among the school students related learning English: lack of vocabulary, wrong pronunciation, grammar, mother tongue use daily, less practice and others. Besides, they also have a psychological problem such as lack motivation. The main factors of students’ problems because the environmental factors which do not support them to implement English in daily language communication.